Three years of struggle in Spain, 1936-1939: the Spanish revolutionary unions speak - F.A.I. (Organization : Spain) ; Federación Ibérica de Juventudes Libertarias (Freedom Press)
1939-04 DE05-09-014 206/3/5/10/15(xiv)